MAKE THE MOST OF CURRENT TECHNOLOGY TO PRESERVE LOCAL HERITAGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 2 February 2016 – The latest technology presents the best means to preserve local heritage, including traditional healing and other forms of local wisdom practised by Malaysian communities.